Wall shear stress calculations based on 3D cine phase contrast MRI and computational fluid dynamics: a comparison study in healthy carotid arteries. (12th May 2014) - Cibis, Merih; Potters, Wouter V.; Gijsen, Frank J. H.; Marquering, Henk; vanBavel, Ed; van der Steen, Antonius F. W.; Nederveen, Aart J.; Wentzel, Jolanda J.
<x xml:space="preserve">Abstract</x> Wall shear stress (WSS) is involved in many pathophysiological processes related to cardiovascular diseases, and knowledge of WSS may provide vital information on disease progression. WSS is generally quantified with computational fluid dynamics (CFD), but can also be calculated using phase contrast MRI (PC‐MRI) measurements. In this study, our objectives were to calculate WSS on the entire luminal surface of human carotid arteries using PC‐MRI velocities (WSSMRI) and to compare it with WSS based on CFD (WSSCFD). Six healthy volunteers were scanned with a 3 T MRI scanner. WSSCFD was calculated using a generalized flow waveform with a mean flow equal to the mean measured flow. WSSMRI was calculated by estimating the velocity gradient along the inward normal of each mesh node on the luminal surface. Furthermore, WSS was calculated for a down‐sampled CFD velocity field mimicking the MRI resolution (WSSCFDlowres). To ensure minimum temporal variation, WSS was analyzed only at diastole. The patterns of WSSCFD and WSSMRI were compared by quantifying the overlap between low, medium and high WSS tertiles. Finally, WSS directions were compared by calculating the angles between the WSSCFD and WSSMRI vectors. WSSMRI magnitude was found to be lower than WSSCFD (0.62 ± 0.18 Pa versus 0.88 ± 0.30 Pa, p < 0.01) but closer to WSSCFDlowres (0.56 ± 0.18 Pa, p < 0.01). WSSMRI patterns matched well with those of WSSCFD. The overlap area was 68.7 ± 4.4% in low and 69.0 ± 8.9% in high WSS tertiles. The angles between WSSMRI and WSSCFD vectors were small in the high WSS tertiles (20.3 ± 8.2°), but larger in the low WSS tertiles (65.6 ± 17.4°). In conclusion, although WSSMRI magnitude was lower than WSSCFD, the spatial WSS patterns at diastole, which are more relevant to the vascular biology, were similar. PC‐MRI‐based WSS has potential to be used in the clinic to indicate regions of low and high WSS and the direction of WSS, especially in regions of high WSS. Copyright © 2014 John Wiley & Sons, Ltd.